Aspects of tree veneration around the cult of John the Baptist in medieval Syria and Spain (10th–14th centuries CE). Issue 2 (3rd July 2022) - Duque, Adriano
Abstract : The practice of tree veneration is often either dismissed as a superstitious "magical" rite or relegated to the realm of idiosyncratic belief. This article proposes a way of understanding tree veneration as a meaningful social practice. Taking the veneration of John the Baptist in Mandean, Christian, and Islamic religion from the tenth to the thirteenth centuries CE, the paper first gives a phenomenological analysis of the different rituals around Saint John's sacred trees. Then, guided by the legend of John the Baptist, it develops a phenomenology of tree substitution, showing that the act of prayer builds on and essentially modifies ordinary cases of shared veneration, and how rituals convey different significations and symbolic meanings.